An open label, prospective, observational study on role of homoeopathic medicine in geriatric age group of patients and its analysis using Barthel index: - Tomar, Sunita; Tare, Garima; Jaliya, Vishal (International Journal Of Community Medicine And Public Health, 2025)
Background: An ordinal scale called the Barthel scale is used to measure how well people conduct activities of daily living (ADL). The likelihood of being able to live at home with some degree of independence increases with a higher score. A study on elderly patients aged 60 to 80 with a variety of illnesses, including dementia, osteoarthritis, benign prostatic hyperplasia, hypertension, diabetes mellitus and stroke, was carried out at Government Homoeopathic Medical College and Hospital in Bhopal, Madhya Pradesh. Methods: To study the role of homoeopathic medicine in geriatric group of patients and its analysis using Barthel Index. It was observational, individualistic, descriptive study. Results: A total of 944 patients were included in the study and after the statistical analysis of data the paired samples t-test results show that there is a statistically significant difference between the "AFTER" and "BEFORE" measurements, with the "AFTER" measurements being significantly higher. The results suggest a highly significant difference between the two groups being compared, with a large effect size. The extremely small p-value (4.076 × 10-151) indicates that the observed difference is very unlikely to have occurred by chance if the null hypothesis were true. Conclusions: It is concluded that homoeopathic medicine seems to be efficacious in treating and managing various kinds of ailments in geriatric group of patients like dementia, osteoarthritis, benign prostatic hyperplasia, hypertension, diabetes mellitus, stroke etc. using Barthel index scoring.